Pattern recognition using multilayer neural-genetic algorithm - Alsultanny, Yas Abbas; Aqel, Musbah M. (Neurocomputing (Amsterdam), 2003)
The genetic algorithm implemented with neural network to determine automatically the suitable network architecture and the set of parameters from a restricted region of space. The multilayer neural-genetic algorithm was applied in image processing for pattern recognition, and to determine the object orientation. The library to cover the views of object was build from real images of (10×10) pixels. Which is the smallest image size can be used in this algorithm to recognize the type of aircraft with its direction The multilayer perecptron neural network integrated with the genetic algorithm, the result showed good optimization, by reducing the number of hidden nodes required to train the neural network (the number of epoch's reduced to less than 50%). One of the important results of the implemented algorithm is the reduction in the time required to train the neural network.